Implementación de un módulo didáctico de transferencia de calor por conducción lineal y radial para prácticas de laboratorio en la asignatura termo aplicada de la carrera de ingeniería en electromecánica de la universidad técnica de Cotopaxi - Cando Cueva, Tatiana Elizabeth (2018)
The work presented in this project involves the transfer of heat by conduction, which is the primary factor that is taken into account for the design of the equipment which allows, through the temperature obtained, to determine the coefficient of heat conduction in metallic materials. The idea of implementing this equipment is due to the new needs of laboratories to be reempowered and to meet the requirements of the current curriculum. The proposed methodology is focused on the selection of different materials for the construction of the conduction heat transfer module, as well as the development of mathematical models to determine the conductivity, efficiency and transferred heat flow into the described materials. The laboratory practice will be carried out with the parameters proposed in the methodology; the interpretation of data in tables and graphs, once the different tests have been made to the materials taking into account the operating temperature, which will be constant in each one of the equipment for the axial 170 ° C and radial 90 ° C, also it is disclosed the equipment costs, the benefit and the results obtained from the laboratory practices. The data collected will be real, and with this, the proposed objective of guaranteeing the student's learning in a didactic way is fulfilled